Multipurpose Aggregation in Risk Assessment - Zoltán Kovács; Tibor Csizmadia; István Mihálcz; Zsolt T. Kosztyán (Mathematics, 2022)
Risk-mitigation decisions in risk-management systems are usually based on complex risk indicators. Therefore, aggregation is an important step during risk assessment. Aggregation is important when determining the risk of components or the overall risk of different areas or organizational levels. In this article, the authors identify different aggregation scenarios. They summarize the requirements of aggregation functions and characterize different aggregations according to these requirements. They critique the multiplication-based risk priority number (RPN) used in existing applications and propose the use of other functions in different aggregation scenarios. The behavior of certain aggregation functions in warning systems is also examined. The authors find that, depending on the aggregation location within the organization and the purpose of the aggregation, considerably more functions can be used to develop complex risk indicators. The authors use different aggregations and seriation and biclustering to develop a method for generating corrective and preventive actions. The paper provides contributions for individuals, organizations, and or policy makers to assess and mitigate the risks at all levels of the enterprise.